2021
DOI: 10.3892/mmr.2021.12268
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin promotes siMAD2L2‑induced apoptosis in colon cancer cells

Abstract: The clinical efficacy of colorectal tumor treatment is restricted due to platinum agent resistance. Translesion DNA synthesis (TLS) has been shown to contribute to this resistance; however, the exact molecular mechanism remains unknown. The present study aimed to investigate the possible function of the core of the TLS polymerase mitotic arrest deficient 2 like 2 (MAD2L2) in drug sensitivity, in order to provide a treatment rationale for platinum-based chemotherapy in colon cancer. In the present study, MAD2L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Hypersensitivity to DNA-damaging agents such as cisplatin, carboplatin, melphalan, chlorethamine, doxorubicin, mitomycin c, or γ-irradiation, but not to H 2 O 2 , 5FU, taxol, or vincristine, decreased spontaneous and damage-induced mutation frequency, accumulation of DSBs and increased chromosomal aberrations after DNA damage, and suppressed cisplatin-induced SCE are promoted by REV7 depletion in nasopharyngeal carcinoma cells [ 61 ]. REV7 suppression also sensitizes malignant melanoma, TGCT, and colon cancer cells to cisplatin, doxorubicin, or oxaliplatin, and sensitizes gliomas and esophageal squamous cell carcinoma (SCC) cells to IR [ 86 , 90 , 91 , 101 ]. In addition, tumor-bearing mouse experiments with REV7 -depleted cancer cells also demonstrated suppressed cell proliferation, increased apoptotic cells, and enhanced sensitivity to cisplatin in vivo in ovarian cancer and TGCT cells [ 87 , 91 ].…”
Section: Rev7 In Cancermentioning
confidence: 99%
“…Hypersensitivity to DNA-damaging agents such as cisplatin, carboplatin, melphalan, chlorethamine, doxorubicin, mitomycin c, or γ-irradiation, but not to H 2 O 2 , 5FU, taxol, or vincristine, decreased spontaneous and damage-induced mutation frequency, accumulation of DSBs and increased chromosomal aberrations after DNA damage, and suppressed cisplatin-induced SCE are promoted by REV7 depletion in nasopharyngeal carcinoma cells [ 61 ]. REV7 suppression also sensitizes malignant melanoma, TGCT, and colon cancer cells to cisplatin, doxorubicin, or oxaliplatin, and sensitizes gliomas and esophageal squamous cell carcinoma (SCC) cells to IR [ 86 , 90 , 91 , 101 ]. In addition, tumor-bearing mouse experiments with REV7 -depleted cancer cells also demonstrated suppressed cell proliferation, increased apoptotic cells, and enhanced sensitivity to cisplatin in vivo in ovarian cancer and TGCT cells [ 87 , 91 ].…”
Section: Rev7 In Cancermentioning
confidence: 99%
“…Oxaliplatin’s cytotoxic effects, on the other hand, are still poorly studied in detail. Many chemotherapeutic drugs, including oxaliplatin, have been demonstrated to cause apoptosis in tumour cells [ 111 ]. Since a medication’s cellular target is dependent on the accumulation in cancer cells, the clinical efficacy of oxaliplatin may be influenced by variables that regulate its accumulation due to its expression by tumour cells or by biological barriers that impact drug disposition.…”
Section: Chemotherapeutic Drug Delivery Using Nanoparticlesmentioning
confidence: 99%
“…Therefore, the ubiquitin host system cooperates the immune system to ght bacteria 9 . Newly research has found that enhancing the lives of PSMD13 protein may promote apoptosis and increase the expression of Bax and Bak, while the expression of Bcl2 is, on the contrary, thus expanding the apoptosis rate of colon cancer cells 10 . PSMD13 regulates the production of in ammatory mediators, and the production of INOS, COX-2, NO, and prostaglandin Escherichia 2 substantially decreased after PSMD13 gene knockout 7 .…”
Section: Introductionmentioning
confidence: 99%